Visible-light-driven photoreduction of CO2 to CO over porous nitrogen-deficient carbon nitride nanotubes. Issue 10 (24th April 2019) - Guo, Shien; Zhang, Hongye; Yang, Peng; Chen, Yu; Yu, Xiaoxiao; Yu, Bo; Zhao, Yanfei; Yang, Zhenzhen; Liu, Zhimin
Abstract : The solar energy-driven photoreduction of CO2 with H2 O to hydrocarbon fuels is an interesting but challenging topic. Abstract : The solar energy-driven photoreduction of CO2 with H2 O to hydrocarbon fuels is an interesting but challenging topic. Herein, we report porous nitrogen-deficient carbon nitride nanotubes with tunable nitrogen vacancies (NCN- T ) for visible-light-driven photoreduction of CO2 to CO in the absence of any cocatalyst and sacrificial reagent. The NCN- T series were prepared via the thermal etching approach, which showed a specific surface area of up to 207 m 2 g −1 and a CO2 uptake capacity of 4.06 wt%. It was indicated that the nitrogen vacancies in NCN- T not only promoted the utilization of visible-light by extending the spectral response range, but also served as centres for capturing photoexcited electrons, hence, efficiently inhibiting the recombination of radiative electron–hole pairs. As a consequence, the NCN- T catalysts achieved the highest CO formation rate of 43.9 μmol g −1 h −1, which was >9 times higher than that obtained over the bulk counterpart.